2014
DOI: 10.1161/cir.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Status of Cardiovascular Disease and Stroke in Hispanics/Latinos in the United States

Abstract: Background and Purpose This American Heart Association (AHA) scientific statement provides a comprehensive overview of current evidence on the burden cardiovascular disease (CVD) among Hispanics in the United States. Hispanics are the largest minority ethnic group in the United States, and their health is vital to the public health of the nation and to achieving the AHA’s 2020 goals. This statement describes the CVD epidemiology and related personal beliefs and the social and health issues of US Hispanics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
301
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(309 citation statements)
references
References 345 publications
6
301
2
Order By: Relevance
“…For example, there were significantly higher smoking scores (ie, fewer smokers) among Mexican‐American women. Indeed, the lower rates of CVD mortality among Hispanics as compared with NH whites—known as the Hispanic Paradox—are contrary to the generally higher risk factor burden and CVD incidence among Hispanics 3. It has been posited that cultural context may contribute to this particular CVH resiliency, despite disparate access to some health resources 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there were significantly higher smoking scores (ie, fewer smokers) among Mexican‐American women. Indeed, the lower rates of CVD mortality among Hispanics as compared with NH whites—known as the Hispanic Paradox—are contrary to the generally higher risk factor burden and CVD incidence among Hispanics 3. It has been posited that cultural context may contribute to this particular CVH resiliency, despite disparate access to some health resources 23.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐Hispanic (NH) blacks have higher incidence of coronary heart disease, heart failure, stroke, and overall CVD mortality as compared with NH whites 1, 2. CVD burden in Hispanics as compared with NH whites is mixed; whereas Hispanics have lower overall CVD mortality, incidence rates for coronary heart disease and stroke appear to be higher 3. However, US Hispanics are an aggregated ethnicity that includes multiple heritage groups, and previous research has shown highly varying prevalence of CVD and CVD risk factor prevalence by Hispanic background 4.…”
Section: Introductionmentioning
confidence: 99%
“…The term Hispanic refers to a heterogeneous group of individuals of any race who have origins in Mexico, the Caribbean, Central America, South America, or other Spanish‐speaking countries 1. Although Hispanic persons share the same Spanish language, their histories of migration into the United States differ, affecting patterns of settlement, social profiles, and health factors 2, 3, 4, 5, 6.…”
mentioning
confidence: 99%
“…Research indicates that a majority of recurrent stroke cases can be prevented by better control of modifiable risk factors [5]. However, Hispanics (a term we used interchangeably with Latinos) face a disparate burden of stroke and stroke risk factors in comparison to non-Hispanic whites [6,7,8]. For example, hypertension, diabetes, and limited physical activity account for more strokes among Hispanics than any other racial or ethnic group [9,10,11].…”
Section: Introduction Backgroundmentioning
confidence: 99%